PKM Activity Providing Social Assistance to Al-Mujtahid Ii Islamic Boarding School in Punggur Kecil Village, Sungai Kakap District, Kubu Raya Regency: PKM Kegiatan Pemberian Bantuan Sosial Kepada Pondok Pesantren Al-Mujtahid Ii Di Desa Punggur Kecil Kecamatan Sungai Kakap Kabupaten Kubu Raya - Sudirman Sudirman; Adi Suryadi; Ignasia Debbye Batuallo; Azzomarayosra Wicaksono; Arkanudin Arkanudin (Universitas Lancang Kuning, 2023)
The problems faced by the Al-Mujtahid Islamic Boarding School II Punggur Kecil Village, Sungai Kakap District in developing and carrying out religious education activities other than the operational support facilities they have are still inadequate, also in meeting basic needs in order to ease the burden of parenting students, they still need to get support from donors. This PKM is to provide social assistance (bansos) in the form of basic necessities to the Al-Mujtahid II Islamic Boarding School which is packaged in the form of basic necessities, an act of social care in the world of education towards the condition of the community, especially those related to education. With the social assistance packaged in the form of basic necessities, it is hoped that the problems faced by this Islamic boarding school can be resolved to some extent by meeting their food needs.